2016
DOI: 10.20319/pijss.2016.s21.16971715
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring as an Hr Intervention to Engage Gen Y Employees

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For instance, by improving the employees’ know-how on customers’ expectations, the overall customer experience can be enriched substantially; thereby hotel’s financial performance and service innovative behavior will dramatically rise. Meanwhile, it has been underscored that stimulating the engagement of hospitality workforce is of fundamental significance (Liu et al , 2022), as engaged workforce has a higher likelihood of being productive, enthusiastic committed, loyal and well-informed about the organization’s goals, work procedure and job requirements (Al-Jabri, 202o; Naim and Lenka, 2016b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, by improving the employees’ know-how on customers’ expectations, the overall customer experience can be enriched substantially; thereby hotel’s financial performance and service innovative behavior will dramatically rise. Meanwhile, it has been underscored that stimulating the engagement of hospitality workforce is of fundamental significance (Liu et al , 2022), as engaged workforce has a higher likelihood of being productive, enthusiastic committed, loyal and well-informed about the organization’s goals, work procedure and job requirements (Al-Jabri, 202o; Naim and Lenka, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it indicates the phenomenon of acquisition of competencies, i.e. learning (Naim and Lenka, 2016b). However, for the contemporary hospitality organizations, it is essential to expand employees' personal, professional and social competencies (Chand, 2010).…”
Section: Competency Development As a Mediatormentioning
confidence: 99%
“…According to all non-family interviewees, they only had a little input to every decision since only the family members that could include in decision making process; they could only give suggestion when it came to the technical things in production process. In fact, all employees want to be emotionally engaged and feel that they are being part of the importance and being connected with business (Naim, 2016).…”
Section: People: International Journal Of Social Sciences Issn 2454-5899mentioning
confidence: 99%
“…A first set of studies emphasises how relational factors enable learning, mainly for the mentee (Bjørnson and Dingsøyr, 2005). A second set of Mentoring programmes studies has questioned the purely positive view of mentoring and has focused on mentoring as a learning practice, emphasising the mutual learning and support between both junior and senior employees (Samarra et al, 2017;Burmeister et al, 2018;Naim and Lenka, 2016). Studies have shown that learning requires partakers to have confidence and mutual trust in one another (Ragins et al, 2000).…”
Section: Introductionmentioning
confidence: 99%